Chemical and elemental composition of big bluestem as affected by ecotype and planting location along the precipitation gradient of the Great Plains - Zhang, Ke; Johnson, Loretta; Nelson, Richard; Yuan, Wenqiao; Pei, Zhijian J.; Wang, Donghai (My University, 2012)
Three big bluestem ecotypes from central Kansas (Cedar Bluffs and Webster populations), eastern Kansas (Konza and Top of the World populations), and Illinois (12Mile and Fults populations), as well as the Kaw cultivar, were harvested from four reciprocal garden planting locations (Colby, Hays, and Manhattan, KS; and Carbondale, IL) and evaluated for their chemical (glucan, xylan, arabinan, lignin and ash) and elemental (carbon, oxygen, hydrogen, nitrogen and sulfur) compositions. The objective of this research was to study the effects of ecotype and planting location on the chemical and elemental compositions of big bluestem along the Great Plains precipitation gradient (∼1200 to 400 mm mean annual precipitation). All the populations revealed a large variation in cellulose (31.8–36.5%), hemicellulose (24.96–29.74%), lignin (14.4–18.0%), carbon (47.3–51.3%), and nitrogen (4.91–6.44%). Planting location had significant effects on both chemical and elemental compositions of big bluestem. Ecotype had significant effects on glucan, xylan, lignin, and ash contents as well as on carbon, oxygen, and hydrogen elemental fractions. In addition, the interaction between ecotype and planting location had significant effects on glucan, lignin, and hydrogen. Planting location had a greater effect on chemical and elemental compositions than the ecotype and interaction between location and ecotype. The total sugar content of the big bluestem (regardless of ecotype) increased as the Great Plains precipitation gradient increased from west to east. Annual precipitation, growing degree days and potential evapotranspiration in 2010 explained up to 97%, 88% and 80% of the variation in compositions, respectively
Keywords: Big bluestem; Chemical composition; Elemental composition; Ecotype; Reciprocal common garden